2017
DOI: 10.1159/000455807
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Randomized Controlled Study of Antioxidant Supplementation with Lutein for Chronic Central Serous Chorioretinopathy

Abstract: Purpose: To investigate functional and morphological changes in patients with chronic central serous chorioretinopathy after supplementation with antioxidants containing lutein or a placebo. Procedures: One hundred eyes of 100 patients were randomly divided into 2 groups, one taking tablets with lutein plus other antioxidants and the other taking a placebo for 6 months. Best-corrected visual acuity (BCVA) and the subfoveal fluid height on optical coherence tomography were measured. Results: Seventy-nine patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 44 publications
0
9
0
3
Order By: Relevance
“…Eine kürzlich veröffentlichte randomisierte, placebokontrollierte Studie postuliert eine positive Wirkung von oral gegebenen Antioxidanzien und Lutein auf die Resorption der subretinalen Flüssigkeit bei Patienten mit CCS. Weitere randomisierte, placebokontrollierte Studien werden vonnöten sein, um diesen für die asiatische Bevölkerung postulierten Effekt zu validieren, sodass eine Therapie aktuell nicht empfohlen werden kann [105].…”
Section: Antioxidanzien Und Luteinunclassified
“…Eine kürzlich veröffentlichte randomisierte, placebokontrollierte Studie postuliert eine positive Wirkung von oral gegebenen Antioxidanzien und Lutein auf die Resorption der subretinalen Flüssigkeit bei Patienten mit CCS. Weitere randomisierte, placebokontrollierte Studien werden vonnöten sein, um diesen für die asiatische Bevölkerung postulierten Effekt zu validieren, sodass eine Therapie aktuell nicht empfohlen werden kann [105].…”
Section: Antioxidanzien Und Luteinunclassified
“…[ 46 ] A multicentre study investigating the effect of lutein supplement on 100 eyes of 100 patients with chronic CSC showed reduced subretinal fluid with significantly improved BCVA. [ 47 ] A retrospective review of 29 eyes of 23 patients treated with finasteride reported significant reduction in SRF and improvement in BCVA, although it was also noted a rate of 37.5% recurrence after cessation of treatment. [ 48 ]…”
Section: Emerging Treatments For Cscmentioning
confidence: 99%
“…Eine kürzlich veröffentlichte randomisierte placebokontrollierte Studie postuliert eine positive Wirkung von oral gegebenen Antioxidanzien und Lutein auf die Resorption der subretinalen Flüssigkeit bei Patienten mit CCS. Weitere randomisierte placebokontrollierte Studien werden vonnöten sein, um diesen für die asiatische Bevölkerung postulierten Effekt zu validieren, sodass eine Therapie aktuell nicht empfohlen werden kann [77].…”
Section: Antioxidanzien Und Luteinunclassified